Investigation on the Characteristics of a Combination Microflow Control Valve. (12th April 2021) - Wang, Yuqi; Liu, Xinhui; Chen, Jinshi; Han, Yafang; Liu, Siyuan; Huo, Dongyang
Abstract : Flow control valves have broad application prospects in aviation hydraulic systems. This paper proposes a combination microflow control valve (CMCV) instead of the traditional valve to optimize the performance. Influences of structural parameters of CMCV on its characteristics are numerically investigated to determine the static and dynamic characteristics of CMCV. The calculation results indicate that there is a negative feedback control between stages of the flow regulator, the orifice pressure drop is compensated, and the flow regulation deviation is reduced. The orifice area and the flow regulator valve port area have significant effects on flow characteristics. The diameter of orifice, the spring stiffness, the number of throttle holes, and the ultimate displacement of sleeve are positively correlated with the flow rate stability value of the valve. The valve port flow area gradient and initial overlap of the flow regulator affect the flow rate fluctuation range and response time of CMCV.